The National Structure of the Romanian Population at the 1st December 2021 Census - George-Bogdan TOFAN; Adrian NIȚĂ (Studia Universitatis Babeş-Bolyai: Geographia)
The National Structure of the Romanian Population at the 1st December 2021 Census. This study aims to focus on the spatial distribution of the 21 ethnic groups at the level of geographical-historical provinces and counties, based on the final results recorded at the Population and Housing Census of 1st December 2021. Compared to the total stable population of 19,053,815 inhabitants, the Romanian ethnic group has a percentage of 77.68%, followed at a great distance by the Hungarians (5.26%) and the Roma (3.00%), after which the other 18 ethnic groups (Ukrainians, Germans, Turks, Russian-Lipovans, Tatars, Serbs, Slovaks, Bulgarians, Croats, Greeks, Italians, Jews, Czechs, Poles, Ruthenians, Armenians, Albanians and Macedonians) all together represent only 0.92% of the total population. There is also the category Other ethnicity (Csangos, Gagauz, Chinese and other ethnicities from intra- and extra-community states) with 0.10%, as well as the category Unavailable information, which includes an important segment of the population of 13.04%.